Analysis of Healthcare Quality Management Systems in Hospitals: A Literature Review Based on Accreditation Standards and Patient Satisfaction - Muh Arfah; Suci Safwa Salsabila; Aulia Apriliani; Nur Akifa Sartika Putri; Andi Sri Adinda (Universitas Cahaya Prima, 2026)
Hospital healthcare plays a vital role in ensuring the sustainability and effectiveness of national health systems. The implementation of a Quality Management System (QMS) has become a strategic approach to improving service consistency, patient safety, and organizational performance. Hospital accreditation serves as an external evaluation mechanism that promotes compliance with established standards and continuous quality improvement. This study employed a qualitative descriptive literature review approach to examine the relationship between accreditation standards, QMS implementation, service quality, and patient satisfaction. A total of 48 articles were initially identified from relevant databases. After duplicate removal and title–abstract screening, 27 articles remained. Following full-text assessment based on inclusion and exclusion criteria, 5 articles were finally selected for analysis.The findings indicate that accreditation strengthens structured procedures, documentation systems, patient safety culture, and internal monitoring processes. Accredited hospitals tend to demonstrate better procedural compliance and service delivery. Furthermore, service quality dimensions—reliability, responsiveness, assurance, empathy, and tangibles—are strongly associated with patient satisfaction. The novelty of this study lies in integrating accreditation standards, QMS implementation, service quality, and patient satisfaction into one analytical framework.In conclusion, integrating accreditation standards with continuous quality improvement and patient-centered strategies is essential to achieving sustainable service quality and higher patient satisfaction in hospitals.